High-severity fire now dominant in California forests - Mitchell J. Hung; A. Park Williams (Proceedings of the National Academy of Sciences, 2026)
Fire severity exerts crucial ecological controls in many forests globally. In California, where annual forest-fire area has increased dramatically in recent decades, understanding how burn severity is changing is essential for informing environmental policy and management. We developed remotely sensed high-resolution maps of severity for 4,391 forest fires to assess trends and drivers of burn severity across California’s forests from 1985–2024. We observed that historically dominant low-severity and ecologically restorative fire was increasingly replaced by high-severity stand-replacing fire, which became the most common severity class beginning in 2012. This regime shift indicates that forested areas are increasingly burning at severity levels they are unlikely to survive. Redistribution toward high-severity fire was strongest in high-biomass forests, implicating heavy fuel loads due to fire exclusion as an amplifier of tree mortality. Importantly, California’s forests provide a vast array of ecosystem services, including the regulation of climate and the water cycle, biodiversity support, and timber and recreation revenue. Thus, the growing dominance of high-severity forest fire is likely to impose significant socioeconomic costs on California.